Social Integration, Art therapy and educational process with teenagers - Ormezzano, Graciela; Gallina, Franciele S. (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2009)
This article is an approximation to a part of the gotten results in an ethnographic study of case and with a qualitative approach; talks about educative process in an art therapy workshop with Brazilian teenagers in conflict with law and permits some thoughts about social integration and violence.